2014
DOI: 10.1111/1471-0528.13192
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin treatment for secondary recurrent miscarriage: a randomised, double‐blind, placebo‐controlled trial

Abstract: Objective To determine whether infusions with intravenous immunoglobulin (IVIg) during early pregnancy increase live birth rate in women with secondary recurrent miscarriage compared with placebo.Design A single-centre, randomised, double-blind, placebocontrolled trial.Setting A tertiary centre for recurrent miscarriage in Copenhagen, Denmark.Population A group of 82 women with unexplained secondary recurrent miscarriage and at least four miscarriages.Methods Women were randomly assigned to repeated infusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 34 publications
2
77
1
Order By: Relevance
“…In the largest placebo-controlled trial that included 82 women with unexplained secondary RPL, LBRs were comparable between IVIg (54.8%) and placebo (50%) 135. A recent meta-analysis of 11 randomized trials in women with URPL also showed no difference in LBR between IVIg and placebo (RR: 0.92, 95% confidence interval [CI]: 0.75–1.12, P =0.42) 136.…”
Section: Unexplained Rpl (Urpl)mentioning
confidence: 96%
“…In the largest placebo-controlled trial that included 82 women with unexplained secondary RPL, LBRs were comparable between IVIg (54.8%) and placebo (50%) 135. A recent meta-analysis of 11 randomized trials in women with URPL also showed no difference in LBR between IVIg and placebo (RR: 0.92, 95% confidence interval [CI]: 0.75–1.12, P =0.42) 136.…”
Section: Unexplained Rpl (Urpl)mentioning
confidence: 96%
“…[28][29][30] The immunosuppressive properties of IVIG could induce downregulation of B-cell function, 31 and involve in the anti-idiotypic suppression of autoantibodies, 32 prevention of Fc receptormediated phagocytosis, 33 increase of regulatory function of T cells, 34 obstruct of complement fixation, 35 and regulation and alteration of cytokine and cytokine receptor expressions, signaling and functions. 37 One meta-analysis described that IVIG caused to considerably increased live birth rate in RM women with immune anomalies. The trials are very heterogeneous, particularly in terms of the number of previous miscarriages experienced by the women and the IVIg dosages.…”
Section: Discussionmentioning
confidence: 99%
“…After systematic evaluation, more than half of cases of RPL were classified as unexplained [27]. Several meta-analyses of randomized clinical trials of IVIG therapy for unexplained RPL failed to prove its effectiveness [202128]. …”
Section: The Validity Of Ivig Therapy For Each Indicationmentioning
confidence: 99%
“…Even though a meta-analysis of IVIG for women with RPL and randomized controlled trials have not demonstrated a beneficial effect [192021], IVIG is commonly prescribed for women with reproductive failure. However, there is no consensus on the indication and treatment protocol for IVIG in those women.…”
mentioning
confidence: 99%